Optimal integration of pneumatic artificial muscles with vacuum-jammed surfaces to characterise a novel reconfigurable moulding system - Habibi, Hossein; Land, Patrick; Ball, Michael J.; Troncoso, David Alatorre; Branson, David T. (Elsevier, 2018)
Producing mould tooling systems is a considerable proportion of manufacturing cost and time, especially for low volume productions. Producing a reconfigurable mould to shape surfaces into complex geometries with multiple curvatures would obviate the need to design and fabricate individual moulds for different products. Current reconfigurable mould tooling systems are mainly variations on a ‘bed of pins’ design through differing patterns of actuated pins. These systems are heavy, mechanically complex and expensive to manufacture. Soft pneumatic actuators such as Mckibben muscles, also known as pneumatic artificial muscles (PAMs) are recognised for their high strength to weight ratio, ease of manufacture and low cost. In this work, PAMs are used to influence a soft elastomeric surface, allowing the formation of spatial curved profiles. This thin, hollow surface is packed with a granular medium that exhibits jamming under the negative pressure of a vacuum. This allows the flexible surface to transform to a rigid surface of greatly increased stiffness with a specific geometry for moulding purposes. This paper presents the design, experimental development and experimental performance of two sample prototypes to actualizes the idea of such adaptable moulding tools. The prototypes contain different actuator arrangements to form jamming surfaces into diverse, simple-to-complex 3D profiles. In addition, the kinematic performance for one of the prototypes is shown by a numerical model. Future work on this system will tailor it for production of fibre carbon composites.